انخفاض مقاومة البيتون عالي المقاومة باستخدام إحضارات محلية و رماد السيليكا على الضغط عند تعرضه لدرجات حرارة عالية - منير الأطرش; زكائي طريفي; مطيع عبشي (Tishreen University, 2016)
يضم هذا البحث لمحة عن الاختبارات القياسية العالمية لعينات بيتونية معرضة لدرجات حرارة عالية, و دراسة تغير مقاومة البيتون المحلي عالي المقاومة عند تعرضه لدرجات حرارة عالية, وذلك بعد إنتاج خلطة بيتونية محلية, وتسخين العينات في فرن خاص تم تصنيعه لهذه الغاية, ومن ثم اختبار العينات المسخنة وغير المسخنة, والتعرف على نسب الانخفاض في المقاومة وقيمها, والحصول على بيانات خاصة بهذه الإحضارات. حيث تم في هذا البحث تصميم خلطة بيتونية من الاحضارات المحلية واستخدام مادة رماد السيليكا والمدن عالي الفعالية وذلك وفق طرق تصميم الخلطات المعتمدة وتعريضها إلى درجات حرارة عالية في فرن كهربائي صنع خصيصا لهذا البحث وبما ينسجم مع تجارب سابقة تم كسر العينات على الضغط والتعرف على تأثير ارتفاع الحرارة This paper is devoted to investigate the effect of high temperatures on the behavior and compression resistance of rectangular high-resistance concrete samples. In this study, rectangular samples with dimensions of (15X15X15 cm) have been made and after 28 days they have been burned in a special oven, then cooled down in the air. The exposition of high-resistance concrete samples which made of local sand and aggregate and use silica fumeoiiuk to high temperatures has led to a reduction and lose in the compressive resistance of this samples. When the temperature was 350 c, the reduction in the compressive resistance was about 13%, and at the temperature of 450c, the reduction was about 36%, and at the temperature of 850c, the reduction was about 72%. Therefore, we have to take this reduction of compressive resistance in the concrete elements seriously when they exposed to fire, so we can take the right decisions about rehabilitation or conservation or replacement of this elements.